ENTERIC FEVER IN TRAVELERS: AN UPDATED INSIGHT - Mehta, Varshil (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Enteric fever is a broad term used to represent typhoid and paratyphoid fever which is caused by S. typhi and S. paratyphi respectively. The most common cause being S. typhi, overall. However, S. paratyphi is known to infect the travelers at a higher rate. Indian subcontinent being one of the most endemic region, it is always beneficial for the travelers to get immunized while traveling to these areas. However, Vaccination to S. paratyphi is not yet available, hence travelers often fall prey to the disease. The morbidity is often high but mortality is very rare, especially due to first line treatment drugs like ceftriaxone, nalidixic acid and floroquinolones (if patients are sensitive to it). Recently, it was observed that Multi-drug resistance (Resistance to at least ampicillin, chloramphenicol and trimethoprim-sulfamethoxazole]) was limited to Typhi isolates and was increased at an exponential rate. Hence, with increasing resistance to these drugs, developing vaccines or new drugs against these bacteria, remains an area of prime interest. Keywords: Salmonella typhi, Salmonella paratyphi, Enteric fever, Traveler.